Protección del desarrollo de productos elaborados en la carrera de agroindustria a través del secreto industrial de los diferentes procesos de elaboración de chorizo de cerdo ahumado extra sarta mediante la inclusión de extractos cítricos orgánicos y zumo de remolacha (Beta vulgaris). - Calderón Heredia, Erick Sebastián (2022)
Due technological innovations, the world has become globalized, as well as upfront and inclusive, sharing new research on public platforms, disseminating it at all levels, which is why it is important to keep certain secret processes. The purpose of this integrating project is legal protection of industrial secret of different production processes of smoked pork chorizo extra sarta, through inclusion of organic citrus extracts and beet juice (Beta vulgaris), on behalf of the Universidad Técnica De Cotopaxi. This project began with the compilation of information from undergraduate research project, carried out previously for its respective analysis, process methodology, preparation of the flow chart, formulation and process material balances for their respective protocolization at Third Notary Latacunga, Cotopaxi province and respective registration of industrial secret as intellectual property at SENADI in the name of the institution. The used methodology was: non-experimental, applied and inductive. The costs of protection were considered. The entire process was carried out with tutor direction, teacher and technicians of the National Service of Intellectual Rights. Concluding that industrial secret is an effective way to protect developed product and it can be very valuable, if it is diligently protected and used strategically; this will benefit compliance with quality requirements requested by CACES